Bat diversity and its distribution in Mount Gutom Protected Landscape, Zamboanga del Norte, Philippines (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Lama JMN, Caballero EB, Mondejar EP. 2023. Bat diversity and its distribution in Mount Gutom Protected Landscape, Zamboanga del Norte, Philippines. Biodiversitas 24: 5495-5502. Bats play an indispensable role in the balance of the ecosystem in their habitats, which range from the seaside to mountains, caves, and rivers. This study surveyed the flying mammals of Mt. Gutom Protected Landscape, Zamboanga del Norte, Philippines, on April 12-23 and December 7-20, 2022. Mist netting was used to sample bats at the four sampling sites, with a total sampling effort of 126 net-nights. A total of eight species (n=330 individuals) representing two families was recorded. This includes Lesser Dog-faced fruit bat (Cynopterus brachyotis), Philippine Dawn bat (Eonycteris robusta), Philippine Pygmy fruit bat (Haplonycteris fischeri), Harpy fruit bat (Harpyionycteris whiteheadi), Dagger-toothed long-nosed fruit bat (Macroglossus minimus), Greater Musky fruit bat (Ptenochirus jagori), Lesser Musky fruit bat (P. minor), and Horsfield’s myotis (Myotis horsfieldii). The Lesser Dog-faced fruit bat (Cynopterus brachyotis) was the most abundant species in Mt. Gutom, with relative abundance of 40.91% (n=135 individuals). Mt. Gutom also supports endemic species, with 62.5% endemicity, and a Vulnerable species (Eonycteris robusta) was documented only in Site 2 (a mixed secondary dipterocarp forest). Moreover, sampling site 3 (secondary dipterocarp forest) recorded the highest abundance (RA=44.24%) and species diversity index (H’=1.376) among the four sampling sites. The results suggest that Mt. Gutom supports a diverse species of bats and conservation measures are needed to protect the remaining habitats in the area.